International Police Organizations: Interpol and Europol Overlap and Interaction - Gergis, Nancy (Eastern Mediterranean University EMU, 2017)
The purpose of this thesis is to explore the correlation between the International Criminal Police Organization (Interpol) and the European Police Office (Europol) structurally, operationally, and functionally. to scrutinize the proposition that a distinction between these two organizations is not just about the extent of membership but also about the functions, roles, and the degrees of homogeneity and autonomy of the organizations. The methodological approaches employed are the fragmentation of international organizations and international law, regime theory, and bureaucratization theory of policing. Interpol and Europol perform dissimilar roles in the international system being instruments, arenas, and actors. At the same time, they do perform significant functions by providing international standardized norms and rules, responsible for rule application and exchange of information. This represents respective international regimes and different models of governance and administration in the field of combating transnational crimes. Keywords: International Police Organizations, Interpol, Europol, Regimes, Fragmentation, Bureaucratization, Autonomy and Homogeneity

ÖZ: Bu tezin esas amacı uluslararası polis teşkilatları İnterpol ve Europol‟ü incelemektir. Bu teşkilatların çakışmaları ve etkileşimleri yapısal; işlevsel; ve fonksiyonel olarak araştırılmıştır. Bu tezde uluslararası teşkilatların ve uluslararası hukukun ayrışma teorisi, ve polisliğin bürokratikleşme ve rejim teorisi kullanılacaktır. Kullanılan kıyaslama araçları İnterpol ve Europol vasıtalarının,alanlarının ve aktörlerinin rolleridir. Ayrıca İnterpol ve Europol‟ün bu çalışmada incelenen fonksiyonları kurallar, kural-koyuculuk, kuralların uygulanması, ve karşılıklı bilgi alışverişidir. Bu yüzden bu çalışmanın birincil odak noktası İnterpol ve Europo‟ün kurumsal ayrışma, rejim karmaşaları, otonomi, ve homojenlik elementleridir. Bu tez birincil ve ikincil bilgilerden yaralanıp daha çok yayınlanmış kitaplar, Europol sözleşmesi, İnterpol‟ün anayasası ve esasen çok yönlü ve iki yönlü anlaşmalar, gazete ve dergi makaleleri içermektedir. Anahtar Kelimeler: Uluslararası Polis Teşkilatları, İnterpol, Europol, Rejimler, Ayrışma, Bürokraikleşme, Otonomi, Homojenlik
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of International Relations, 2017. Supervisor: Assoc. Prof. Dr. Wojciech Forysinski.
Keywords: Political Science and International Relations; Police-International cooperation; International Criminal Police Organization (INTERPOL); European Pollice Office (EUROPOL); International Police Organizations; Interpol; Europol; Regimes; Fragmentation; Bureaucratization; Autonomy and Homogeneity